Effects of Caffeine Ingestion on Anaerobic Capacity in a Single Supramaximal Cycling Test - Miyagi, Willian E. [UNESP]; Bertuzzi, Romulo C.; Nakamura, Fabio Y.; Poli, Rodrigo A. B. de [UNESP]; Zagatto, Alessandro M. [UNESP] (Frontiers Media Sa, 2018)
The aim of this study was to verify the effects of caffeine on anaerobic capacity estimated by the sum of the estimated glycolytic [E-[La]] and phosphagen [E-PCr] metabolism based on blood lactate and excess post-oxygen consumption responses (AC([La-]+EPOCfast)). Fourteenmale cyclists were submitted to a graded exercise test to determine themaximal oxygen uptake ((V)over dotO(2max)) and intensity associated with. (V)over dotO(2max) (i(V)over dotO(2max)). Subsequently, the participants performed two supramaximal efforts at 115% of i(V)over dotO(2max) to determine the AC([La-]+EPOCfast), after previous supplementation with caffeine (6 mg.kg(-1)) or a placebo (dextrose), in a cross over, randomized, double blind, and placebo-controlled design. The time to exhaustion was higher in the caffeine (186.6 +/- 29.8 s) than in the placebo condition (173.3 +/- 25.3 s) (p = 0.006) and a signi fi cant correlation was found between them (r = 0.86; P = 0.00008). Significant differences were not found between AC([La-] + EPOCfast) values from the placebo (4.06 +/- 0.83 L and 55.2 +/- 5.7 mL.kg(-1)) and caffeine condition (4.00 +/- 0.76 L and 54.6 +/- 5.4 mL.kg(-1)); however, a significant correlation was observed only for AC([La-]+EPOCfast) expressed in absolute values (r = 0.74; p < 0.002). The E-[La] and E-PCr also presented no significant differences and they were signi fi cantly correlated (r = 0.82 and r = 0.55, respectively; p < 0.05). We conclude based on the overall comparison of mean values between two treatments that acute caffeine ingestion improves the time to exhaustion but does not affect anaerobic capacity estimation.
Keywords: caffeine; anaerobic capacity; performance; running; ergogenic aids